Towards Sustainable Building
XVI, 254 p.
Keywords: This volume contains the extended versions of selected papers presented at the first Mediterranean Conference "Sharing Knowledge on Sustainable Building" held at the Polytechnic ofBari in December 1999, supported by the National Research Council of Italy. The publication of this book was made possible through the efforts of the contributing Authors. Other people have provided invaluable support for the conference and for the preparation of this volume; in particular, I wish to thank Antonella Lerario for providing support in the final editing of the text and images. 1 As reported in Boonstra and Rovers (200 I) , people spend a great deal of time inside buildings; therefore, decisions about design, construction, use, maintenance, renovation, demolition, reuse and recycling of buildings have a huge impact on the sustainable development of our society. Technical aspects, however, should be supported by adequate policies, developed with appropriate tools and driven by meaningful challenges. For people involved in sustainable buildings, the conceptual frameworks, studies and experiences collected in this volume, organized into three parts - "Policies", "Tools" and "Challenges" - will help to advance knowledge allowing them to adopt and more efficiently implement such innovations sooner.